2019
DOI: 10.1038/s41467-019-13489-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary decidual zone formation requires Scribble for pregnancy success in mice

Abstract: Scribble (Scrib) is a scaffold protein with multifunctional roles in PCP, tight junction and Hippo signaling. This study shows that Scrib is expressed in stromal cells around the implantation chamber following implantation. Stromal cells transform into epithelial-like cells to form the avascular primary decidual zone (PDZ) around the implantation chamber (crypt). The PDZ creates a permeability barrier around the crypt restricting immune cells and harmful agents from maternal circulation to protect embryonic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 43 publications
2
39
0
Order By: Relevance
“…Uterine epithelium and stroma are two major components of the endometrium, and their interactions are involved in the process of the receptivity acquisition 1,18,19 . Uterine epithelium and stroma have independent and mutual functions to support uterine receptivity and embryo implantation 1,[18][19][20] . Although the previous literature demonstrated the significance of uterine STAT3 in embryo implantation 14 , the role of epithelial and stromal STAT3 in the process of embryo implantation remains unclear.…”
mentioning
confidence: 99%
“…Uterine epithelium and stroma are two major components of the endometrium, and their interactions are involved in the process of the receptivity acquisition 1,18,19 . Uterine epithelium and stroma have independent and mutual functions to support uterine receptivity and embryo implantation 1,[18][19][20] . Although the previous literature demonstrated the significance of uterine STAT3 in embryo implantation 14 , the role of epithelial and stromal STAT3 in the process of embryo implantation remains unclear.…”
mentioning
confidence: 99%
“…The finding that macrophages remain close to Cnr1 -/- Cnr2 -/- implantation chambers prompted us to examine the formation of the PDZ on day 6 of pregnancy. PDZ formation requires Scrib signaling ( Yuan et al, 2019 ), yet the Scrib positive domain is much reduced in Cnr1 -/- Cnr2 -/- females ( Figure 4a ). This result is also supported by the presence of blood vessels, revealed by immunostaining of FLK1, a reliable marker of blood vessels, in the Cnr1 -/- Cnr2 -/- PDZ on day 6 of pregnancy ( Figure 4b ).…”
Section: Resultsmentioning
confidence: 99%
“…Because the PDZ is avascular, this zone is normally devoid of maternal immune cells, and protects embryos from circulating maternal insults ( Tung et al, 1986 ). Recently we have shown that Scribble (Scrib), a scaffold protein and a component of the planar cell polarity (PCP), plays a key role in PDZ formation ( Yuan et al, 2019 ). However, molecular regulation in the formation of the PDZ is still far from clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On D4, in the P4-primed uterus, E2 regulates new functions essential for embryo implantation; these are the expression of glandular Lif which is viewed as the final step in the acquisition of uterine receptivity and which, together with P4, E2 induces stromal cell proliferation and decidualization (7,53,54). Stromal cell decidualization begins on the afternoon of D5 in cells surrounding the implantation chamber in the antimesometrial region of the uterus; this forms the primary decidual zone (PDZ), a transient tissue that is well developed by D6 but has undergone demise by D8 (55)(56)(57)(58). This PDZ is avascular and is enriched in intercellular tight junctions, gap junctons, and adherens junctions, and it creates a permeability barrier around the implantation chamber, isolating the embryo from immune cells and harmful molecules present in the maternal circulation (59,60).…”
Section: Discussionmentioning
confidence: 99%